Long intergenic non‐coding RNA 511 correlates with improved prognosis, and hinders osteosarcoma progression both in vitro and in vivo. Issue 5 (1st January 2020) - Qiao, Suchi; Qi, Ke; Liu, Chang; Xu, Changli; Ma, Jun; Xu, Xinmin; Li, Cheng; Wang, Zhiwei
Abstract: Background: This study aimed to investigate the correlation of long intergenic non‐coding RNA 511 (LINC00511) with clinicopathological characteristics and overall survival (OS) in osteosarcoma patients and to explore its function in osteosarcoma in vitro and in vivo. Methods: Tumor tissues and adjacent tissues from 45 osteosarcoma patients were acquired, and LINC00511 expression was detected. In vitro, LINC00511 expression was detected in osteosarcoma cell lines and osteoblast cell line. LINC00511 overexpression‐treated (OE‐LINC00511) and nonsense overexpression‐treated (OE‐control) MG‐63 and Saos‐2 cells were cultured, followed by the assessment of cell proliferation, apoptosis, migration, and invasion. In vivo, tumor weight and volume were measured in OE‐LINC00511 and OE‐control xenografted mice. Results: LINC00511 expression was decreased in tumor tissues compared with adjacent tissues ( P  < .001), and its high expression correlated with increased tumor cell necrosis rate to neoadjuvant chemotherapy ( P  = .025) and prolonged OS ( P  = .010). In vitro, LINC00511 expression was decreased in osteosarcoma cell lines (including MG‐63, U‐2OS, Saos‐2, and HOS) compared with osteoblast cell line (All P  < .001). Cell proliferation was decreased at 48 hours (Both P  < .01) and 72 hours (Both P  < .001) (in MG‐63 and Saos‐2 cells); cell apoptosis was increased ( P  < .05) (in Saos‐2 cells); cell migration and invasion were decreased (All P  < .01) (in MG‐63 cells and Saos‐2 cells) in OE‐LINC00511 compared with OE‐control. In vivo, tumor volume was reduced at week 4 ( P  < .001), week 5 ( P  < .001), week 6 ( P  < .001) in OE‐LINC00511 compared with OE‐control. Tumor weight was declined in OE‐LINC00511 than OE‐control ( P  < .001). Conclusions: LINC00511 acts as a potential biomarker and therapeutic option for osteosarcoma.